Seasonality and season of birth effect in the UK Biobank cohort. Issue 6 (28th March 2020) - Didikoglu, Altug; Canal, Maria Mercè; Pendleton, Neil; Payton, Antony
Abstract: Objectives: Humans live in environments that reduce the impact of seasonal cues. However, studies suggest that many aspects of human biology, such as birth, metabolism, health, and death are still annually rhythmic. Methods: Using UK Biobank, a large (N = 502 536) population‐based resource, we investigated the influence of seasonality on birth rate, basal metabolic rate, health, reaction speed, and sleep. We also investigated the association between season of birth and regional brain volumes, basal metabolic rate, health, reaction speed, and sleep. Results: Our results showed that annual birth rate peaks in April and May. Individuals had the highest basal metabolic rate in December and January. Poorer subjective general health and slower reaction time were observed in May. Susceptibility to insomnia showed an opposite trend that peaked in autumn and winter. People reported shorter periods of sleep, easier waking, earlier chronotype, more daytime dozing, and napping in summer compared with winter. Our results suggest that season of birth may influence later‐life characteristics. We also observed that the effect of season of birth is in the opposite direction of the seasonal rhythm for basal metabolic rate, reaction time, and insomnia. Moreover, our analysis showed that prevalence of allergy is higher among people born in spring compared to autumn. Conclusions: Overall, our findings indicate a significant effect of seasonality on a range of human traits and that early‐life seasons appear to have an effect on health and behaviors in adulthood.